2014
DOI: 10.1002/hep.27235
|View full text |Cite
|
Sign up to set email alerts
|

Treatment response in the PIVENS trial is associated with decreased hedgehog pathway activity

Abstract: Hedgehog (Hh) ligand production by ballooned hepatocytes drives nonalcoholic steatohepatitis (NASH) progression in mice. The NIDDK-sponsored PIVENS trial (NCT00063622) showed that Vitamin E (VitE) improved NASH. We investigated whether VitE treatment and improvement in NASH were associated with changes in Hh pathway activity. Immunohistochemistry (IHC) was performed on both pre- and post-treatment liver biopsies of 59 PIVENS patients randomized to VitE (n=30) or placebo (n=29). Sonic Hh (Shh) ligand-producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 49 publications
(140 reference statements)
1
48
0
Order By: Relevance
“…More recently, Hedgehog has been proposed as an important intermediate regulatory node, which facilitates paracrine crosstalk between damaged hepatocytes and hepatic progenitor cells that expand and contribute to fibrogenesis and myofibroblast activation [163]. The PIVENS trial, which randomized NASH patients to placebo, pioglitazone, or vitamin E, suggested histological response was strongly correlated with loss of the important Hedgehog ligand, Sonic hedgehog [164].…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 97%
“…More recently, Hedgehog has been proposed as an important intermediate regulatory node, which facilitates paracrine crosstalk between damaged hepatocytes and hepatic progenitor cells that expand and contribute to fibrogenesis and myofibroblast activation [163]. The PIVENS trial, which randomized NASH patients to placebo, pioglitazone, or vitamin E, suggested histological response was strongly correlated with loss of the important Hedgehog ligand, Sonic hedgehog [164].…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 97%
“…Inhibiting or eliminating smoothened, a G proteincoupled receptor mediating signalling in the presence of sonic hedgehog ligand 238 , resulted in reduced macrophage activation and expression of proinflammatory genes in a mouse model 239 . Analysis of liver biopsies from patients with NASH enrolled in the PIVENS trial showed that response to treatment (vitamin E) was inversely associated with levels of sonic hedgehog 240 . Prenatal supplementation with vitamin E has not been studied in the context of NAFLD; however, it has not been associated with positive outcomes in other inflammatory models such as allergy 241,242 .…”
Section: Targeting the Gut–liver Axismentioning
confidence: 99%
“…In vitro models proved that expression of Sonic and Indian Hh mRNAs and proteins are induced in ballooned hepatocytes and showed that these cells release biologically active Hh ligands that are able to trigger Hh signaling in Hh-target cells (Rangwala et al, 2011; Kakisaka et al, 2012; Machado et al, 2014). Further, treatments that improve liver injury and hepatocyte ballooning in humans with NASH also reduce hepatic accumulation of both Hh-positive hepatocytes and Gli2-positive stromal cells (Guy et al, 2014). Other types of cells that accumulate in injured livers during hepatic wound healing are also capable of producing Hh ligands, such as immune cells (e.g., NKT cells (Syn et al, 2012) and macrophages (Pereira et al, 2013)), activated progenitor cells (Jung et al, 2007), activated hepatic stellate cells/myofibroblasts (Sicklick et al, 2005; Yang et al, 2008; Choi et al, 2009) and activated liver sinusoidal endothelial cells (Xie et al, 2013).…”
Section: Physiology Of the Hedgehog Pathway In The Livermentioning
confidence: 99%